Performance of infill reinforced concrete masonry unit wall with addition of waste pavement as aggregate material - Hasan D.; Alisibramulisi A.; Habulat A.; Bakar S.; Ramli M.Z.; Musir A.A. (American Institute of Physics Inc., 2023)
Concrete masonry unit commonly known as concrete block has been widely used in Malaysia. Concrete masonry units (CMU), commonly referred to as concrete blocks, are the most common construction material utilized throughout the Malaysia and neighboring region for exterior walls of conventional structures. A binding agent such as mortar and concrete are able to increase the compressive strength. Additional material use in this experimental will increase the probability strength of concrete masonry unit. Pavement waste are used as an additional aggregate material in order to decrease the space of landfill. By recycling this pavement waste, it help to reduce the quantity of disposed materials. So, there is an initiative to use this pavement waste in structural work since there is an increase the number of construction work in Malaysia. The concrete masonry wall has significant crack pattern when applied with static loading. This investigation present the result of structural behavior of concrete masonry unit wall and to observe the cracking pattern under static loading. The dimension of wall panel is about 1 meter in height and approximately 1.5 meter in width. Strain gauge and linear variable differential transformer (LVDT) was placed in correct position in order to collect the data. The maximum load was applied where the stress develop on the specimen and the data was collected. The displacement and stress-strain result was tabulate accordingly by graph and cracking pattern was observed during the experiment. 2018 Author(s).